The Impact of the COVID-19 Pandemic on Foreign Body Ingestion Trends in Children: A Comparison of the Pre-Pandemic Period to 2020. Issue 3 (28th April 2022) - Geibel, Elyse; Pasman, Eric; Nylund, Cade; Rudolph, Bryan; Reeves, Patrick
Abstract : Foreign body ingestion (FBI) among children is associated with morbidity and mortality. We used the National Electronic Injury Surveillance System to compare FBI trends from 2017–2019 to 2020 during the spread of SARS-CoV-2. The pandemic and associated stay-at-home orders were associated with uptrends in button battery and magnet ingestions but unchanged total FBI trends.